2020
DOI: 10.26502/jcsct.5079089
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hedgehog Pathway in Female Cancers

Abstract: Background: The hedgehog pathway (HH) is one of the key regulators involved in many biological events. Malfunction of this pathway is associated with a variety of diseases including several types of cancers. Methods: We collected data from public databases and conducted a comprehensive search linking the HH pathway with female cancers. In addition, we overviewed clinical trials of targeting HH pathway in female cancers. Results: The activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The Hedgehog pathway is one of the key regulators involved in many biological events. Malfunction of this pathway is associated with various diseases, including several types of female cancers ( 427 ). An initial study demonstrated that elevated expression of SMO and GLI 1, the key members of the Hedgehog pathway, was observed in leiomyosarcoma relative to normal myometrium and uterine fibroid tumors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The Hedgehog pathway is one of the key regulators involved in many biological events. Malfunction of this pathway is associated with various diseases, including several types of female cancers ( 427 ). An initial study demonstrated that elevated expression of SMO and GLI 1, the key members of the Hedgehog pathway, was observed in leiomyosarcoma relative to normal myometrium and uterine fibroid tumors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…GLI1 has only an activator form, while GLI2 and GLI3 have both activators (GLI2A and GLI3A) and repressor forms (GLI2R and GLI3R) [ 12 ]. GLI members act as the nuclear effectors at the end of the pathway, which is responsible for regulating the expression of downstream target genes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously shown that SMO inhibitors can be combined with other inhibitors or chemotherapeutic agents to effectively inhibit breast cancer progression ( 38-40 ). In particular, a clinical trial targeted SMO in the hedgehog signaling pathway in female patients with breast cancer ( 41 ). The results of these trials suggested that targeting this pathway can be an effective treatment option for patients with cancer ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a clinical trial targeted SMO in the hedgehog signaling pathway in female patients with breast cancer ( 41 ). The results of these trials suggested that targeting this pathway can be an effective treatment option for patients with cancer ( 41 ).…”
Section: Discussionmentioning
confidence: 99%